Comparison of the predictive validity of the Alberta Infant Motor Scale and Infant Neurological International Battery in low-birth-weight infants: a prospective longitudinal study - Narayan, Amitesh; Sai Anand, Polisetti Siva; Karnad, Shreekanth D.; Alammari, Abdulaziz (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2025)
Introduction. This study aims to test the predictive validity of the Infant Neurological International Battery (INFANIB) and the Alberta Infant Motor Scale (AIMS) against the Peabody Developmental Motor Scale-2 (PDMS-2) at 4, 8 and 12 months of age in low birth weight (LBW) infants.Methods. Motor development in 18 LBW infants was examined prospectively at 4, 8 and 12 months. A professional investiga-tor assessed the motor development of these infants using the AIMS, INFANIB and PDMS-2. The validity of the results was assessed using Friedman and Wilcoxon signed-rank tests on the total raw scores of PDMS-2, AIMS and INFANIB at the three distinct age points. The chi-square test was used to calculate the association between INFANIB and AIMS with PDMS-2 for normal and LBW infants at each age point.Results. The INFANIB and AIMS scores were both associated with PDMS-2 at all three age points. However, INFANIB dem-onstrated a higher predictive validity for PDMS-2 in LBW infants than AIMS.Conclusions. The INFANIB has greater predictive validity than AIMS for assessing motor outcomes in LBW infants at 4, 8 and 12 months.
Keywords: Infant Neurological International Battery; Alberta Infant Motor Scale; motor outcomes; low birth weight infants; predictive validity; Peabody Developmental Motor Scale-2